Implementasi Keindahan Nusantara Dalam Mengikuti Program Pertukaran Mahasiswa Merdeka (PMM) Angkatan Dua - Saragih, Elza L.L.; Sitorus, Parlindungan; Pardede, Surya Dharma; Sirait, Maya Lestari; Purba, Jusbinaraya; Sitohang, Lusi Roina (STAI Denpasar Bali, 2023)
Indonesia is a country that has diversity, starting from culture and customs in the era of globalization, so it is necessary for students of the nation's generation to preserve culture through the independent education program (MBKM), independent campus learning, one of the second batch of independent student exchange programs launched by the Ministry of Education and Culture, many universities are encouraging students to take part in one of them is HKBP Nommensen University Medan which sends its students to existing universities starting from Sabang-Merauke which are student destination universities namely Jakarta State University and Trunojoyo Madura University. The students carry out cross-major lecture activities, in the independent student exchange program students also carry out Nusantara module activities which aim to get to know the cultural diversity that exists in Indonesia through this students can get to know the culture at the destination university and even make friends with various ethnic groups so that students know the beauty of life various. Students register through the MBKM account through file registration following the exam selection until departure to the destination university. So by participating in the second batch of domestic independent student exchange activities, students become more enthusiastic about getting to know culture, preserving culture, learning across new science majors and even adding to relationships and taking care of and respecting one another.